Myth or magic: the impact of financial technology on financial inclusion in Africa - Yengeni, Sandisiwe (Graduate School of Business (GSB), 2021)
With the worldwide focus on financial inclusion to decrease poverty levels by banking the unbanked, understanding how to facilitate the banking of the previously unbanked in developing countries has become a globally topical issue. To contribute to this discussion from the perspective of Africa, the following paper endeavours to compute financial inclusion indices (FII) for 36 African countries. The paper leverages a model developed by Cámara and Tuesta (2014), using a two-stage Principal Component Analysis with definitions for financial inclusion variables from Sarma (2008). Upon computing the indices, we then endeavour to study the relationship between financial technology (fintech) and financial inclusion by running a regression analysis between fintech variables and the financial inclusion indices. As expected, we find that the highest financial inclusion levels are in the Southern and East African regions, with the lowest in Central Africa. The introduction of mobile money has had a significant impact on financial inclusion levels, particularly in East Africa. Our analysis also finds that the usage variable is critical in understanding the depth of financial inclusion. While this is so, there is still a great need for improvements across financial access, usage and availability in Africa. The regression analysis confirms this assessment, showing that overall, the use of mobile accounts has a positive and significant relationship with financial inclusion. At the same time, the use of digital payments for existing accounts also improves financial inclusion but to a lesser extent. The distinction between the impact of mobile banking and digital payments is an important one given that ownership of mobile banking increases the number of people with access to financial services while using digital payments merely deepens and enhances the usage of existing account holders. Macroeconomic factors of economic growth and banking sector development also are significant for financial inclusion, though to a lesser degree. This paper recommends the study of what impacts the sub-indices both positively and negatively, and how countries can maximise each sub-index, as it is an important focus area for policymakers who are looking to improve financial inclusion levels for their respective countries. We further recommend the development of a unified taxonomy on financial inclusion and its measurements. The role of policymakers would be to propel forward the formulation of this taxonomy, working with all the relevant stakeholders.